Warrior women : the anonymous Tractatus de mulieribus - Gera, Deborah Levine. (Mnemosyne, Supplements, 1997)
This study analyzes the anonymous Tractatus de Mulieribus , a brief, virtually unknown Greek work, telling of fourteen outstanding women, Greek and barbarian, notable for their intelligence, initiative and courage. The first part of the book is a comprehensive introduction to the treatise and includes - in addition to the original text and an English translation - an examination of both the content and form of De Mulieribus , particularly as a catalogue of women. The times, methods, and purposes of the anonymous author are also investigated. Commentary-essays on the individual women then follow. A wide variety of sources are utilized in order to sketch the fullest possible portrait of each of these lively women. This book, the very first study of De Mulieribus , is a useful introduction to a remarkable treatise.